Nigerian Pidgin English in Cape Town: exploring speakers’ attitudes and use in diaspora - Umana, Beauty Friday Happy (Linguistics, 2020)
Nigerian Pidgin English is widely spoken in different parts of the country and “has been called the native language of a substantial population of people in the Niger Delta, particularly in the Sapele and Warri areas” (Igboanusi, 2008: 68). According to Balogun (2012: 90), “Nigerian Pidgin English has emerged as the most widely spoken language of inter and intra communication among Nigerians and across diverse ethnic groups that do not share a common language”. The language plays a major role in youth culture and most Nigerians speak the language. There is a general belief by some Nigerians that Nigerian Pidgin English is a colloquial form of English that is mostly spoken by those whose Standard English proficiency has not fully developed (Agheyisi, 1971:30). The government has continued to ignore it “despite the fact that Nigerian Pidgin is in most respects the most logical choice for a national language [and] official attitudes towards Nigerian Pidgin remain negative, perpetuating erroneous notions inherited from the colonial period that Nigerian Pidgin is some form of ‘broken English’” (Faraclas 1996: 18). Also, the general attitudes held by Nigerians regarding the language can be described as ambivalent with majority leaning towards the negative attitude more. This project investigated if the Nigerians who find themselves in a different geographical space like Cape Town still hold negative attitudes towards Pidgin English and whether they abstained from speaking the language or speak it freely. The study also sought to establish if those who may have held negative attitudes towards Nigerian Pidgin English while in Nigeria now hold a different attitude since being in Cape Town. The study employed both quantitative and qualitative methods in form of online questionnaires and semi structured interviews involving 38 participants to investigate the uses of and attitudes towards Nigerian Pidgin English. The findings revealed that the attitudes towards Nigerian Pidgin English do not show significant difference from that held by Nigerians within Nigeria. The participants in this study held negative attitudes towards Nigerian Pidgin English in formal domains and positive attitudes towards the language in informal domains. These same attitudes were obtainable among Nigerians living in Nigeria. The data analysis revealed that the Nigerians in this study use the language in their daily activities for different purposes. The hegemonic perspective on Pidgins being an informal language that can serve only informal purposes was also present among some of the Nigerians that formed part of this study. Although some thought that the language can go beyond informal domains, the majority thought otherwise. All the participants use Nigerian Pidgin English mainly to communicate with their friends, family members and other Nigerians they encounter despite living far away from home where other languages exist. Also, the analysis revealed that all the participants considered the language to be an important aspect of their Nigerian identity and togetherness in the diaspora. This indicates a significant difference between those in the diaspora and those in Nigeria, because those in the diaspora appreciate and think there is a greater need for Nigerian Pidgin English outside the country. The data suggested that the reason for this shift in attitude is because speaking the language bridges the gap between home and abroad.